Determinants of the Utilization of Elderly Integrated Healthcare Center Services in the Kassi Kassi Health Center Working Area of Makassar City - Suci Rahmadani; Balqis Balqis; Hadrianti H.D Lasari; Nur Annisa Hamka (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2022)
The number of elderly people in Indonesia is expected to increase from 26.83 million (9.92%) in 2020 to 63.32 million (19.9%) in 2045. Judging from the risk of disease that will be experienced by the elderly and its effect on the dependency ratio of the elderly population, then the government provides integrated healthcare center services for the elderly. The Kassi-Kassi Health Center has the highest number of elderly people in Makassar City, but an average of <70% indicates that the elderly are still less active in utilizing the posyandu. This study aims to analyze the determinants of the utilization of elderly integrated healthcare center services at the Kassi Kassi Health Center in Makassar City. The method used in this research is quantitative with a type of analytic survey and cross-sectional design. The research sample was 110 elderly people in the Kassi Kassi Health Center working area. Data were analyzed by Chi-square test. The results of the analysis showed that knowledge (p=0.000), healthcare beliefs (p=0.019), and illness perception (p=0.050) were related to the utilization of elderly integrated healthcare center services. Meanwhile, the availability of health facilities (p=0.186), distance (p=1.000), and waiting time (p=0.702) were not related to the utilization of elderly integrated healthcare center services. So it can be concluded that knowledge, beliefs, and perceptions of pain are related to the utilization of elderly integrated healthcare center services at the Kassi Kassi Health Center in Makassar City.